2014
DOI: 10.4236/fns.2014.51011
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Analysis Critical Control Point (NACCP): Hazelnut as a Prototype of Nutrigenomic Study

Abstract: The aim of this study is to apply the Nutrient Analysis Critical Control Point (NACCP) process to ensure that the highest nutrient levels in food can determine a beneficial effect on the health of the consumer. The NACCP process involves a sequence of analysis and controls that depart from raw material production to the evaluation of the effect of nutrition on health. It is articulated through the following points: 1) identification of nutrient level in the food; 2) identification of critical control points (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Thus the recovery and enhancement of ecotypes imply not only the enlargement of the basic germplasm and the availability of useful genes, but offer new economic possibilities for local market and potential industrial applications. The lipid fraction is a key factor in determining the hazelnut quality and storability, affecting the taste and the nutritional properties and numerous evidences highlighted its beneficial effect on human health (Di Renzo et al 2014). However the enhancement of cultivars with high-quality attributes meet the demand of hazelnut confectionary industries and consumers with positive implication on the competitiveness of the European products in the international market.…”
Section: Biochemical Characterization Of Hazelnut Germplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the recovery and enhancement of ecotypes imply not only the enlargement of the basic germplasm and the availability of useful genes, but offer new economic possibilities for local market and potential industrial applications. The lipid fraction is a key factor in determining the hazelnut quality and storability, affecting the taste and the nutritional properties and numerous evidences highlighted its beneficial effect on human health (Di Renzo et al 2014). However the enhancement of cultivars with high-quality attributes meet the demand of hazelnut confectionary industries and consumers with positive implication on the competitiveness of the European products in the international market.…”
Section: Biochemical Characterization Of Hazelnut Germplasmmentioning
confidence: 99%
“…Hazelnuts are generally low in saturated fatty acids (SFA), and high in monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids (oleic, linoleic, linolenic, palmitic, and stearic acids), where oleic is the major fatty acid. The atocopherol, that is the active form of vitamin E, helps to lower the risk of certain chronic diseases by protection against heart disease and has an antioxidant function (Salas-Salvadó and Megias 2005;Di Renzo et al 2014).…”
Section: Biochemical Characterization Of Hazelnut Germplasmmentioning
confidence: 99%
“…Although the number of subjects enrolled in our study is acceptable in this instance [1], much greater numbers are required to definitively confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Although beneficial effects are generally attributed to nuts, each species has its own specific nutrition and nutraceutical profile that may provide different kinds [11]. Among the three major tocopherols identified (α-, β-, γ-tocopherols), α-tocopherol is the most active form in human and animal tissues [31] [32] due to the substitution pattern of the methyl groups on the chromanol ring making the hydrogen of the C-6 hydroxyl group especially active, thereby facilitating the transfer of the hydrogen to a peroxyl radical [28] [29].…”
Section: Plasma Measurementsmentioning
confidence: 99%
“…Several epidemiological studies [1] [2] [3] [4] [5] and clinical trials [6]- [11] demonstrated that dried fruit could have an important role on plasmatic lipids, lowering morbidity and mortality related to cardiovascular diseases (CVDs). In 2011, the European Food Safety Authority (EFSA) allowed an Article 13 claim that the consumption of 30 g of walnuts in the context of a balanced diet leads to improvement of endothelium-dependent vasodilatation (available at https://www.efsa.europa.eu/it/efsajournal/pub/2032).…”
Section: Introductionmentioning
confidence: 99%